Disruption of the Extracellular Matrix Progressively Impairs Central Nervous System Vascular Maturation Downstream of β-Catenin Signaling. Issue 7 (July 2019) - Jensen, Lasse D.; Hot, Belma; Ramsköld, Daniel; Germano, Raoul F.V.; Yokota, Chika; Giatrellis, Sarantis; Lauschke, Volker M.; Hubmacher, Dirk; Li, Minerva X.; Hupe, Mike; Arnold, Thomas D.; Sandberg, Rickard; et al.
Abstract : Objective—: The Wnt/β-catenin pathway orchestrates development of the blood-brain barrier, but the downstream mechanisms involved at different developmental windows and in different central nervous system (CNS) tissues have remained elusive. Approach and Results—: Here, we create a new mouse model allowing spatiotemporal investigations of Wnt/β-catenin signaling by induced overexpression of Axin1, an inhibitor of β-catenin signaling, specifically in endothelial cells ( Axin1 iEC − OE ). AOE (Axin1 overexpression) in Axin1 iEC − OE mice at stages following the initial vascular invasion of the CNS did not impair angiogenesis but led to premature vascular regression followed by progressive dilation and inhibition of vascular maturation resulting in forebrain-specific hemorrhage 4 days post-AOE. Analysis of the temporal Wnt/β-catenin driven CNS vascular development in zebrafish also suggested that Axin1 iEC − OE led to CNS vascular regression and impaired maturation but not inhibition of ongoing angiogenesis within the CNS. Transcriptomic profiling of isolated, β-catenin signaling-deficient endothelial cells during early blood-brain barrier–development (E11.5) revealed ECM (extracellular matrix) proteins as one of the most severely deregulated clusters. Among the 20 genes constituting the forebrain endothelial cell-specific response signature, 8 ( Adamtsl2, Apod, Ctsw, Htra3, Pglyrp1, Spock2, Ttyh2, and Wfdc1 ) encoded bona fide ECM proteins. This specific β-catenin-responsive ECM signature was also repressed in Axin1 iEC − OE and endothelial cell-specific β-catenin–knockout mice ( Ctnnb 1-KO iEC ) during initial blood-brain barrier maturation (E14.5), consistent with an important role of Wnt/β-catenin signaling in orchestrating the development of the forebrain vascular ECM. Conclusions—: These results suggest a novel mechanism of establishing a CNS endothelium-specific ECM signature downstream of Wnt-β-catenin that impact spatiotemporally on blood-brain barrier differentiation during forebrain vessel development. Abstract : Supplemental Digital Content is available in the text.